Highly oriented MOF thin film-based electrocatalytic device for the reduction of CO2 to CO exhibiting high faradaic efficiency. Issue 40 (7th September 2016) - Ye, Lu; Liu, Jinxuan; Gao, Yan; Gong, Chenghuan; Addicoat, Matthew; Heine, Thomas; Wöll, Christof; Sun, Licheng
Abstract : A monolithic, highly electrochemically efficient Re-based metal–organic framework (MOF) thin film has been deposited onto a conductive FTO electrode by liquid-phase epitaxy. Abstract : A monolithic, highly electrochemically efficient Re-based metal–organic framework (MOF) thin film has been deposited onto a conductive FTO electrode by liquid-phase epitaxy. The X-ray diffraction (XRD) analysis reveals the presence of a highly oriented film grown exclusively along the [001] direction. This epitaxially-grown SURMOF exhibits an extremely high faradaic efficiency of 93 ± 5% when operated as an electrocatalyst for the reduction of CO2 to CO. In addition, the obtained current densities of the high-quality monolithic coatings exceed 2 mA cm −2, a value at least one order of magnitude larger than that reported for previous electrocatalytically active MOF thin films.